The Good German? German Colonial Fantasies in Indonesia in Rudolf Utsch’s Trilogy - Lisda Liyanti; S.M. Gietty Tambunan; Lily Tjahjandari (Journal of Language and Literature, 2025)
The relationship between Germany and Asia is characterized by its complexity and uniqueness. Unlike other European nations, Germany established close connections with Asia by drawing inspiration from its rich cultural heritage. Germany’s historical background, being overpowered and defeated by France at the beginning of its formation to nationhood, led German thinkers and philosophers to seek sources of national self-identity other than those imbued with antiquity and Western culture. Germany's perception of itself about the East (as well as other regions) can be understood through the lens of German colonial fantasies, which depict Germany as a benevolent colonizer capable of establishing harmonious colonies. This concept of colonial fantasy is dynamic and evolves in line with German historical stages. In this study, we will examine Rudolf Utsch's three-part series of German adolescent adventure texts set in Indonesia by employing a textual analysis approach and focusing on the concept of colonial fantasy by Susanne Zantop. The research outcomes suggest that both German characters were depicted as benevolent colonizers, yet their efforts to establish a harmonious colony proved unsuccessful. Several biases stemming from colonial fantasies are discovered, including gender bias, the marginalization of local characters, and an imbalance in the portrayal of space and location.